Impact of educational intervention on pressure ulcer reporting system among tertiary hospital nurses in Jordan - Emran, Abdalla Abu Aqoulah (2019)
Background: Pressure ulcer (PU), which is a critical health issue, appears to be a common sight within the contexts of Jordan and the Middle East region. Cases of pressure ulcers pose a significant health problem amongst hospitalised patients. To worsen matters, Jordanian nurses have been claimed to possess poor quality of nursing documentation, especially in light of pressure ulcers. As such, inadequate knowledge, skills, and motivation have emerged to be the most crucial factors that have led to acquisition of the necessary quality nursing documentation pertaining to pressure ulcers. Nursing documentation concerning pressure ulcers has become an integral segment within the nursing care domain, primarily because patient records detail one’s journey along the healthcare process and offer vital information pertaining to the accountability of the staff that provides treatment. Good quality of record keeping enhances the quality of patient care. On the contrary, poor nursing documentation leads to misinterpretation, compromised safety amidst patients, and relentless medical errors. Incomplete nursing documentation of pressure ulcer may lead to dramatic deterioration of a patient’s health, increment in workload for nurses, misconceptions, and ineffective communication amongst nurses and with other practitioners. Objective: The aim of this study was developed, implemented, and evaluate the impact of educational intervention on nurses’ knowledge, skills, and motivation, as well as on the quality of nursing documentation in light of Pressure ulcer across Jordan’s Ministry of Health tertiary hospitals. Methods: The study carried out the quasi-experimental repeated measure upon two groups; experimental and control groups, wherein 54 nurses were placed in each group. The nurses were selected to represent a list of wards, namely surgical, medical, intensive care unit, and orthopaedic wards. Stratification and simple random sampling techniques were employed to select 54 nurses for each group. The intervention was carried out at the selected hospital and was divided into two sessions, which are: lecture, and workshop. The intervention incorporated aspects of knowledge, motivation, and skills to enhance the quality of nursing documentation involving pressure ulcer across Jordan’s Ministry of Health hospitals. Pre- and post-intervention, as well as follow-up assessments, were conducted to analyse the research outcomes. The primary findings reflected the quality of nursing documentation for pressure ulcer, which was determined by evaluating two documents concerning pressure ulcer for each participant during each assessment using the Chart Audit Tool. Next, the secondary outcomes displayed the participants’ knowledge, skills, and motivation that were examined via survey questionnaire developed by the researcher. The perprotocol method was applied to assess data of those participants who retained until the end point of the study. One-way MANCOVA, Two-way Repeated MANOVA, and MANCOVA were adopted for data analysis in this study. Results: The response rate obtained for both groups was 83.3%. The results exemplified no statistically significant difference at baseline between intervention and control groups, with respect to participants’ characteristics and research outcomes (p > 0.05). After intervention, significant differences were observed in the research outcomes between and within intervention and control groups after controlling the covariates (p< 0.001). Conclusion: The newly-developed educational intervention was indeed successful in significantly improving the quality of nursing documentation regarding PU, based on the results retrieved from the intervention group. The improvement in quality of nursing documentation regarding pressure ulcer was achieved mainly due to enhanced knowledge, motivation, and skills amidst the nurses in the intervention group.